European total defence : past, present and future - Rongved, Gjermund Forfang, 1980- (Routledge advances in defence studies., 2025)
"This book analyses the origins, experiences and challenges of total defence in Europe, and comprises a broad spectrum of national case studies as well as one international organisation - NATO. The topic of total defence has been brought to the fore by deglobalisation, augmented international tension and the US pivot to Asia, grey-zone threats, Covid-19, and not least by the increased Russian threat during the 2010s, which culminated in the invasion of Ukraine in 2022. The analysis here is based on an in-depth analysis of the four major Nordic countries, the Baltic countries, Poland, Ukraine, Switzerland, and the Netherlands, as well as a perspective from NATO itself. The volume argues that although the activity which we describe as total defence has many labels and various expressions, which follow from each country's own history, geopolitical setting and strategic culture, some aspects of it are to be found in most countries. This is because all countries, at least to some extent, will need their armed forces to rely on civil society in a crisis; however, it is a long way from this to a full-fledged total defence concept. With continued international tension, the need to build resilient societies and the European need to take more responsibility for its own security in a cost-efficient way, the book argues that we should expect total defence to gain importance in the 21st century. This book will be of much interest to students of security studies, defence studies, European politics, and International Relations in general"--